Desain Pemberdayaan Guru Ilmu Pengetahuan Alam Madrasah Ibtidaiyah Melalui Pelatihan Metode Pembelajaran Inovatif - Saputro, Budiyono (IAIN Ponorogo, 2017)
The use of innovative methods by teachers in learning makes students be more critical and can increase studentsâabsorption. Based on the facts in the reality, Islamic Elementary School (MI) teachers are mostly alumni of Islamic Education (PAI). It is proven by the fact that MI teachers throughout Ngablak District, Magelang Regency are dominantly Islamic Education graduates. This type of empowerment is based on qualitative research. The subject of the empowerment is MI class, teachers throughout Ngablak District, Magelang Regency. Data sources are obtained through observation, questionnaire adn Focus Group Discussion. The observation result finds that 100% of science (IPA). Teachers of MI in Ngablak have difficulties in delivering IPA materials using innovative methods and 100% are interested in training. The empowerment design of IPA teachers at MI is as the following: the factual use of IPA learning methods in the field, training in innovative learning methods of IPA and output (application of innovative learning methods in the classroom).Ø¥Ø³ØªØ®Ø¯Ø§Ù Ø£Ø³Ø§ÙÙØ¨ Ù Ø¨ØªÙØ±Ø© Ø§ÙØªÙ ØªØ³ØªØ®Ø¯Ù Ø§ÙÙ Ø¹ÙÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø£Ù ÙØ¬Ø¹Ù Ø§ÙØ·ÙØ§Ø¨ ÙÙ ØªØ²Ø§ÙØ¯ Ø§ÙØ£ÙÙ ÙØ© ÙÙØ²ÙØ§Ø¯Ø© Ø¥Ø³ØªÙØ¹Ø§Ø¨ÙÙ . Ø¥Ø³ØªÙØ§Ø¯Ø§ Ø¥ÙÙ Ø§ÙÙÙØ§Ø¦Ø¹ ÙÙ Ø§ÙÙ ÙØ¯Ø§ÙØ ÙØ«ÙØ±Ø§ Ù Ù Ø§ÙÙ Ø¹ÙÙ ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© Ù ØªØ®Ø±Ø¬ÙÙ Ø¹Ù Ø´Ø¹Ø¨Ø© Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø§ÙØ¥Ø³ÙÙ ÙØ©. ÙÙ Ø§ Ø£Ù ÙÙÙÙ ÙÙ Ù Ø¯Ø±Ø³Ø© Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ©